E-Commerce and Competence, Impact on Business Performance: Empirical Study on Implementation E-Commerce By Students at Pasundan University - Muhammad Ilham; Ina Ratnamiasih (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2021)
The rapid growth of Small Business Enterprise (SME) throughout the Asian economy, especially in Indonesia is partly due to the rapidly developing information technology. The internet has become an important business tool, to the point where even SME utilize e-commerce. SMEs in Indonesia are proven to be the most dynamic and vibrant sector. The use of e-commerce is increasingly widespreading among young people and teenagers. Students–especially college students–are becoming more interested in doing entrepreneurship in between their classes. This research was conducted on students at Pasundan University to determine the influence of e-commerce implementation and student competence on the success of their business. The results showed that e-commerce and competence have a great influence on the success of businesses run by students. Keywords: E-commerce, Competence, Business performance, students